N-Based Polydentate Ligands and Corresponding Zn(II) Complexes: A Structural and Spectroscopic Study - Volpi, Giorgio; Zago, Stefano; Rabezzana, Roberto; Diana, Eliano; Priola, Emanuele; Garino, Claudio; Gobetto, Roberto (Inorganics, 2023)
Herein, the structural and photophysical features of two N-based polydentate ligands and the corresponding Zn(II) complexes are investigated. The obtained compounds were characterized using different spectroscopic techniques and their optical properties are discussed in relation to their chemical structure, defined by single-crystal X-ray diffraction and mass spectrometry. The spontaneous and quantitative complexation, investigated by UV-Vis, fluorescence, NMR, IR spectroscopies and mass spectrometry, makes these N-based polydentate ligands interesting candidates for possible applications in chelation therapy and in Zn(II) sensors.